Sustainable medical and wellness destinations: client, result and innovation-focussed: case studies - Marta-Costa, A. (2013)
In a first client-focussed section (Part 1), Rosa Maria Riveiro Conde, Andrés Mazaira and Patrício Ricardo Soares Costa surveyed customers of northern Portuguese thermal tourism units about their perceptions of the service quality (Chapter 1.1). Joaquim Antunes then relates the results of a questionnaire he distributed among clients at similar businesses in the centre of Portugal in order to highlight the importance of relationship marketing for the medical and wellness tourism branch (Chapter 1.2). Finally, Mei-Ting Hsieh and Timothy Lee present the outcome of their questionnaire survey, carried out at Taiwanese (thermal or mineral spring) spa destinations to determine the most important motivations of clients, and formulate some changes that should be made with regard to the elaboration of more efficient marketing strategies (Chapter 1.3). Maria João Carneiro, Celeste Eusébio, Elisabeth Kastenholz and Helena Alvelos open the second part that concentrates on result-focussed case studies (Part 2) with their analysis of the socioeconomic impacts of a Portuguese social health tourism program at micro and macro levels in Portugal (Chapter 2.1). Timothy Lee ends his critical analysis of the Australian spa hotel industry with a list of very concrete recommendations that can immediately be implemented by medical and wellness tourism business owners and authorities (Chapter 2.2). He and Boram Lim co-authored and obtained similarly concrete outcomes when comparing the same subsector, spa hotels in Australia, with ryokan facilities in Japan (Chapter 2.3). Also very practical are the results of the innovation-focussed case studies (Part 3). Ana Isabel Renda, Júlio da Costa Mendes and Patrícia Oom do Valle suggest that the wellness potential of the spas at hotels in Loulé (Algarve) should also be used by the residents in order to combat seasonality and increase profitability (Chapter 3.1). Using the example of Ourense, the Galician spa capital, Noelia Araújo Vila and José Antonio Fraiz Brea argue for marketing these kinds of destinations by using them as locations for the making of (parts of) soap opera series, films, and so forth (Chapter 3.2). Jesús Raúl Navarro García and Frederico Alvim stress the potential of the natural surroundings for marketing medical and wellness destinations (Chapter 3.3). Finally, analysing the online information search behaviour of Finnish rural well-being tourists, Anja Tuohino and Juho Pesonen come to very practical conclusions that, like all the case studies presented in this book, can inspire other players in the medical and wellness sector (Chapter 3.4).